Comunidades vegetais de área de degelo da Ilha Half Moon, arquipélago das Shetlands do Sul, Antártica - Schmitz, Daniela (2015)
This paper presents the results of the study of plant communities of free ice areas conducted during the austral summer of 2013/2014 and 2014/2015, in February and March, on Half Moon Island in the South Shetlands Archipelago, Maritime Antarctica, aiming to evaluate the distribution and abundance of mosses and lichens, as well as to describe the plant communities occurring in the area, with mapping of the vegetation communities. To assess existing communities on the island through the phytosociology and quantify the species with the highest ecological significance (IES) was used the methodology square (20 x 20cm) of Braun-Blanquet adapted to Antarctic conditions. . The area was mapped using an Astech Promark II® DGPS, yielding sub-metric precision after post-processing with Astech Solutions® software. The number of species totalized 38 bryophyte species, 59 lichens, only one flowering plant (Deschampsia antarctica Desv.) and two macroscopic terrestrial algae. Five plant communities were identified in the island, distributed accordingly to animal occurrence and to sea influence. The plant communities were described as follows: Fruticose lichens community, Moss-carpet community, Muscicolous Lichens community, Crustose lichens community and Moss turf community. The species with the highest IES of the island was Sanionia uncinata (Hedw.) Loeske appearing in 71.78% of sampled squares. The community with the highest richness species was the Moss Carpet, and the most diverse community was the crustosos lichens, which has mostly located in the area where the penguin colonies.